PARTISIPASI CIVIL SOCIETY DALAM UPAYA PEMBERDAYAAN EKS BURUH MIGRAN INDONESIA ASAL LAMPUNG (Studi Pada Serikat Buruh Migran Indonesia Lampung (Administratio, 2017)
ABSTRACT. Good governance is a governmental management in organizing and managing sosial andeconomic resources to develop the growth of the nation. The role of civil society like NGO/ NonGovernment Organizations in Good governance is supporting the participatory development. The lowavailability of employment is one of the problems in the development. This research focuses on theforms of Indonesian Migrant Workers Union (SBMI) participation as a civil society in empowering theformer Indonesian migrant workers from Lampung region.. And also data analyzation. The result of thisresearch showed that the participation of SBMI Lampung in empowering the former Indonesian migrantworkers from Lampung in form of non-physical participation, included: planning, decision making onevaluation and counseling, empowerment, mentoring and rehabilitation; while the physical participation was done in form of procurement necessity for ex-BMI (Indonesian Migrant Workers) such as; materials, machinery and money. In addition, SBMI focused on the process of empowerment in thefield of motivation, self-development, management, resource mobilization and network development. Keywords: Good governance, civil society, SBMI, participation, ex-migrant workers from Lampung.